Correlações lineares e espaciais entre atributos físico-químicos de solos de diferentes ambientes de produção de cana-de-açúcar no Noroeste do Estado de São Paulo - Soria, José Eduardo [UNESP] (2014)
Several factors are responsible for the spatial variability of crop yields, among them, there is the physical and chemical soil attributes. Aimed to evaluate the variability and characterize the spatial dependence between physical and chemical attributes of soils in the northwestern region of São Paulo State, as well as studying the linear and spatial correlations to identify the interactions between such attributes in sugarcane production environments. Data were used soil survey of the Sugarcane Technology Center conducted in the northwestern region of São Paulo State, with provision of data of geographical coordinates, in 638 points belonging to a non-regular grid for the analyzes were collected at depths from 0 to 0.25 and 0,25 to 0,50 m. The granulometric fractions were analyzed, as well as soil fertility and production environments. Descriptive statistics and geostatistic analysis was performed for the attributes. Sugarcane production environments correlate with soil attributes, which are able to help in defining the production potential of the soil. The silt, clay, organic matter, P, K, Ca, Mg, pH, SB, CEC and V% showed positive linear and spatial correlations with the soil production potential. While the proportions of sand, Al3 + and m% had negative correlations with the production potential of the soil . In kriging maps it was possible to areas of lower and higher sugarcane production potential, in other words identify where the best and the worst production environments are. Therefore, with the aid of kriging maps of soil attributes is to develop specific management zones and define the productive potential to an area characterized as the production environment